May I feel said he an opera in three minutes for soprano, tenor and piano four-hands - Sheng, Bright 1955-; Cummings, Edward E. 1894-1962 (G. Schirmer, Inc., 1996)
In one movement. Premiered in May 1996. Printed from manuscript. Custom print edition
Commissioned by the New York Festival of Songs. - Reproduced from holograph. - English words, also printed as text on the title page
Keywords: Musik; Vocal duets with piano, 4 hands / Scores; Operas; Music / Manuscripts / Facsimiles; Cummings, E. E. / (Edward Estlin) / 1894-1962 / Musical settings; Sheng, Bright / 1955- / Manuscripts / Facsimiles; Songs; Chamber music; Scores; Facsimiles